Structural behaviour and design criteria of under-deck cable-stayed bridges subjected to seismic action - Camara,A; Ruiz-Teran,AM; Stafford,PJ (Earthquake Engineering and Structural Dynamics, 2013)
Underdeck cablestayed bridges are very effective structural systems for which the strong contribution of the stay cables under live loading allows for the design of very slender decks for persistent and transient loading scenarios. Their behaviour when subjected to seismic excitation is investigated herein and a set of design criteria are presented that relate to the type and arrangement of bearings, the number and configuration of struts, and the transverse distribution of stay cables. The nonlinear behaviour of these bridges when subject to both nearfield and farfield accelerograms has been thoroughly investigated through the use of incremental dynamic analyses. An intensity measure that reflects the pertinent contributions to response when several vibration modes are activated was proposed and is shown to be effective for the analysis of this structural type. The underdeck cablestay system contributes in a very positive manner to reducing the response when the bridges are subject to very strong seismic excitation. For such scenarios, the reduction in the stiffness of the deck because of crack formation, when prestressed concrete decks are used, mobilises the cable system and enhances the overall performance of the system. Sets of natural accelerograms that are compliant with the prescriptions of Eurocode 8 were also applied to propose a set of design criteria for this bridge type in areas prone to earthquakes. Particular attention is given to outlining the optimal strategies for the deployment of bearings.